A relação homem-trabalho e o desenvolvimento da carreira nas organizações: um estudo entre alunos formandos em administração de empresas na Grande São Paulo - Lacombe, Beatriz Maria Braga (2001)
The present study aims at being a contribution to the issue of the professional career by subjecting it to the point of view of the Man-Work relationship. The construction and management of professional careers within the organizational context are discussed as expressions of the Man-Work relationship, which in its tum exposes the fulfillment of Man' s ontological indeterminacy. Both the tràditional and the emerging form of career are revised and compared in their capacity to fulfil workers ontological openness. In accordance with this, the unfolding of professional careers reveals Man's ontological process of fulfillment which, in the present day society, is developed under the conditions created by the flexible capitalismo The latter brings about a new pattem of career, The management of the professional career in organizations not only reflects the way the process of production is designed but also the conditions under which the individual handles the Man-Work relationship to build his/her career. Within such theoretical grounds an empirical research on the perception of the emerging context for career development is carried out in a population ofBusiness Administration senior students taken from the Great São Paulo. Its particular target was to gather the students' perception of the labor market conditions as an evidence of the way they conceive the development of their professional careers. The findings point out that the.perceptions are limited and are mediated by both the school shift (day or evening) the student attends and the leveI of quality of the school itself